2021
DOI: 10.1007/s00125-021-05609-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of type 2 diabetes in psychiatric disorders: an umbrella review with meta-analysis of 245 observational studies from 32 systematic reviews

Abstract: Aims/hypothesis Estimates of the global prevalence of type 2 diabetes vary between 6% and 9%. The prevalence of type 2 diabetes has also been investigated in psychiatric populations, but a critical appraisal of the existing evidence is lacking, and an overview is needed. This umbrella review summarizes existing systematic reviews of observational studies investigating the prevalence of type 2 diabetes in people with a psychiatric disorder. MethodsWe searched PubMed, EMBASE, PsycINFO and Cochrane Database of Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 77 publications
3
30
1
1
Order By: Relevance
“…These deficits in adapative immunity are consistent with the premature aging hypothesis of depression but extant publications are epidemiological rather than mechanistic in nature. Second, there is a higher rate of cardiovascular, metabolic, inflammatory and other systemic diseases in severe mental illnesses than the general population [ 145 149 ], and these diseases are associated with more severe COVID-19 disease [ 150 152 ]. Nevertheless, the above meta-analyses still show increased (albeit attenuated) mortality in individuals with psychiatric disorders after adjusting for comorbid medical conditions.…”
Section: Depression and Other Psychiatric Disorders As Risk Factors F...mentioning
confidence: 99%
“…These deficits in adapative immunity are consistent with the premature aging hypothesis of depression but extant publications are epidemiological rather than mechanistic in nature. Second, there is a higher rate of cardiovascular, metabolic, inflammatory and other systemic diseases in severe mental illnesses than the general population [ 145 149 ], and these diseases are associated with more severe COVID-19 disease [ 150 152 ]. Nevertheless, the above meta-analyses still show increased (albeit attenuated) mortality in individuals with psychiatric disorders after adjusting for comorbid medical conditions.…”
Section: Depression and Other Psychiatric Disorders As Risk Factors F...mentioning
confidence: 99%
“…In our umbrella review of 32 systematic reviews, we showed that comorbidity of diabetes and mental disorders is common. The prevalence of type 2 diabetes varied between 8% and 40% for different mental disorders [ 6 ]. The prevalence of mental disorders is also high among people with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of this review, there is scant evidence on the prevalence of psychopathology in people with T2DM seeking bariatric surgery. People with T2DM more broadly are known to be at elevated risk of psychopathology and disordered eating [14]. A recent umbrella review identifi ed 32 systematic reviews with 245 primary studies of people with T2DM and measures of psychopathology [14].…”
Section: Introductionmentioning
confidence: 99%
“…People with T2DM more broadly are known to be at elevated risk of psychopathology and disordered eating [14]. A recent umbrella review identifi ed 32 systematic reviews with 245 primary studies of people with T2DM and measures of psychopathology [14]. They revealed the high prevalence rates of psychopathology for people with T2DM: 40% sleep disorder, 21% binge eating disorder, 16 % substance use disorder, 14% anxiety-related disorder, 11% bipolar disorder, 11% psychosis, 9% depression [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation